Public-private partnership projects in infrastructure : an essential guide for policy makers - Delmon, Jeffrey (Cambridge ; New York : Cambridge University Press, 2011)
This book provides an insightful overview of the Public-Private Partnership process and its sectoral implications, taking advantage of the author's extensive experience in PPP transactions.
Includes bibliographical references (p. 235-238) and index.
rua 27/08/13
Loans
Keywords: Infrastructure (Economics); Public-private sector cooperation; Risk assessment; Public contracts